Pregnancy Outcomes in Individuals With Long COVID - Torri D. Metz; Grecio J. Sandoval; Amanda A. Allshouse; Karima Anderson; Alexis Braverman; Krista Coombs; Nathan Erdmann; Adina Gerver; Rachel Hess; Lisa Pappas; Upinder Singh; Brittany D. Taylor; et al. (Obstetrics & Gynecology, 2026)
OBJECTIVE: To evaluate whether there is an association between a maternal classification of Long COVID and adverse pregnancy outcomes. METHODS: RECOVER (Researching COVID to Enhance Recovery)–Adult is a multicenter prospective longitudinal cohort study of adults with and without prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection enrolled from October 2021 to January 2024. This analysis included participants with a SARS-CoV-2 infection and at least one symptom survey for classification of Long COVID status recorded before or during pregnancy. Participants were classified as either likely having Long COVID (LCRI [Long COVID Research Index] score of 11 or higher) or as having Long COVID–indeterminate (LCRI score 0–10), with comparisons made between groups. The primary outcome was preterm birth before 37 weeks of gestation. Secondary outcomes included hypertensive disorders of pregnancy, cesarean delivery, neonatal intensive care admission, and small-for-gestational-age birth weight (below the 10th percentile). Propensity score methods with full matching were used to balance differences in baseline characteristics in estimating an average treatment effect, with a sensitivity analysis estimating the average treatment effect among the treated. RESULTS: Among 603 participants, 118 (19.6%) were classified as likely having Long COVID before or during pregnancy. Participants classified as likely having Long COVID were more likely to have specific adverse social determinants of health (difficulty covering expenses and paying bills, food insecurity, missed care because of cost, medical discrimination) and had higher prepregnancy body mass index (BMI) than those who were classified as having Long COVID–indeterminate. In the primary average treatment effect analysis, there was no association between likely Long COVID and preterm delivery (adjusted outcome rate 8.1% exposed vs 9.6% unexposed, absolute risk reduction [ARR] 0.82, 95% CI, 0.36–1.90) or secondary outcomes. In average treatment effect among the treated sensitivity analyses, likely Long COVID was similarly not associated with preterm delivery (ARR 1.11, 95% CI, 0.60–2.06) but was associated with an increased risk of hypertensive disorders of pregnancy (adjusted outcome rate 39.0% exposed vs 25.9% unexposed, ARR 1.51, 95% CI, 1.12–2.03) but not with other secondary outcomes. CONCLUSION: A classification of likely Long COVID was not significantly associated with preterm birth or several other adverse pregnancy outcomes. However, the association with hypertensive disorders of pregnancy in the average treatment effect among the treated analysis highlights the need for further research.